Psychological predictors of Facebook use: A literature review - Yushi Jiang; Mishal Hasnain Naqvi; Muhammad Hasnain Abbas Naqvi (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
Facebook has experienced remarkable development in recent years, and has become the most commonly used online social networking site (SNS). Due to its increasing importance and popularity among users, the platform has attracted attention from many academicians and researchers. The current paper discusses the key aspects and relevant empirical results of research carried out in relation to Facebook to date by applying a mapping technique as part of a systematic literature review. The method used in this study provides a detailed overview of the context to examine the magnitude and value of existing evidence on Facebook use. The findings offer interesting insights that researchers can use to diversify their investigations into SNS use concerning demographics and certain other antecedents. It also proposes a unique framework by which to understand the as yet unexplored dimensions of social networking sites.
Keywords: M30; M39; 330; Social networking sites; literature review; motivations; personality traits; technology acceptance model; Facebook